2023
DOI: 10.1021/acs.jced.3c00387
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Vapor Pressure and Sublimation Enthalpy of l-serine and l-cysteine

Vladimir B. Motalov,
Mikhail A. Korobov,
Anatoliy M. Dunaev
et al.

Abstract: The crystal–vapor equilibrium for the standard amino acids l-serine and l-cysteine was studied by Knudsen effusion mass spectrometry in the temperature ranges of 387–442 and 361–429 K, respectively. At these relatively low temperatures, the surface degradation of the samples was shown to be minor. The vapor pressure obtained by the Knudsen effusion method was used to calibrate the mass spectrometer. The temperature dependence of the vapor pressure in the investigated temperature range is described by a linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Instrument 1 , which has been employed in our previous works and is described in detail and schematically represented in ref , was used to investigate the molecular composition of the vapor over l - and dl -threonine under electron ionization mode. A cylindrical single-section molybdenum effusion cell with the dimensions of 20 × 10 mm (internal height × diameter) and an effusion hole diameter of 0.5 mm (the ratio of evaporation and effusion areas is about 400; Cell 1) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument 1 , which has been employed in our previous works and is described in detail and schematically represented in ref , was used to investigate the molecular composition of the vapor over l - and dl -threonine under electron ionization mode. A cylindrical single-section molybdenum effusion cell with the dimensions of 20 × 10 mm (internal height × diameter) and an effusion hole diameter of 0.5 mm (the ratio of evaporation and effusion areas is about 400; Cell 1) was used.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent studies, conducted using Knudsen effusion mass spectrometry (KEMS), the thermodynamic parameters of sublimation of L -tryptophan, l - and dl -methionine, l -serine, and l -cysteine were investigated, demonstrating the capabilities of KEMS in studying this class of compounds. The present work continues these investigations and focuses on l - and dl -threonine (2-amino-3-hydroxybutanoic acid; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, L-cysteine is a promising candidate to replace inorganic inhibitors because it is possible to inhibit corrosion, reduce electrical conductivity, and high melting temperature of 240 °C. 14 Some studies using L-cysteine as an additive have been reported. [15][16][17][18] L-cysteine exhibits corrosion inhibition even in severe corrosion environments such as 4 M NaOH solution.…”
mentioning
confidence: 99%